Youth participation in peacebuilding in Gulu District, Northern Uganda: opportunities and challenges - Hartmann, Kris (2016)
Between 1986 and 2006 Northern Uganda was affected by one of the longest running and most brutal armed conflicts in the African history of the 20th century. Despite Ugandan government and NGO efforts the Acholi youth remain a marginalised group in society. The overall youth situation according to the literature is drastic: acute poverty, high unemployment, low literacy rates, socio-economic and political exclusion. Youth play a pivotal role, either they can threaten peace, or can be catalyst for peace and peacebuilding. This qualitative study explored opportunities and challenges for Acholi youth participation in peacebuilding activities. To gain insight into the findings a power analysis with regard to spaces for participation and levels of decision-making was applied. Through four interviews and four Focus Group Discussions with youth actively engaged in peacebuilding, young people described economic marginalisation and lack of awareness as the main challenges to their participation. The youth explicated their opportunities for participation as local and accessible, for example awareness raising on peace issues through drama and dialogues about main conflict drivers. Four interviews with NGO staff contrasted the youth’s experiences, and provided a fuller picture of existing power relations. Both, opportunities and challenges for youth participation are framed by negative youth perceptions and stereotypes from the Acholi community, and the youth’s internalisation of this. Despite of the collective stigmatisation of youth, a gradual change towards appreciation and dialogue has taken place where youth’s impact through their peacebuilding activities was felt. Finally, the study recommends to consider economic empowerment as a mechanism for greater youth participation. If youth are given or create space they positively use it to contribute to, or even to promote greater participation in peacebuilding.